2021
DOI: 10.1177/23328584211014860
|View full text |Cite|
|
Sign up to set email alerts
|

Mobile Learning During School Disruptions in Sub-Saharan Africa

Abstract: School closures due to teacher strikes or political unrest in low-resource contexts can adversely affect children’s educational outcomes and career opportunities. Phone-based educational technologies could help bridge these gaps in formal schooling, but it is unclear whether or how children and their families will use such systems during periods of disruption. We investigate two mobile learning technologies deployed in sub-Saharan Africa: a text-message-based application with lessons and quizzes adhering to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In our view, however, these challenges should not forestall consideration of how evaluation methods from other fields can be adapted for use in RAI tool evaluations. Indeed, research in educational contexts like schools is also subject to changing policies, state standards, students moving from an intervention to control group when enrolling in a new class or school, as well as exogenous shocks like teacher strikes, political violence, and school closures, among others [117]. Conversely, as AI technologies and development paradigms are increasingly incorporated into medical or education interventions, these domains are also starting to consider how to apply their familiar evaluation approaches to AI technologies [e.g., in healthcare, 134,170][e.g., in education, 36], and how to translate insights from RAI to their evaluation practices [e.g.…”
Section: Evaluation Goals and Approaches Outside Of Hcimentioning
confidence: 99%
“…In our view, however, these challenges should not forestall consideration of how evaluation methods from other fields can be adapted for use in RAI tool evaluations. Indeed, research in educational contexts like schools is also subject to changing policies, state standards, students moving from an intervention to control group when enrolling in a new class or school, as well as exogenous shocks like teacher strikes, political violence, and school closures, among others [117]. Conversely, as AI technologies and development paradigms are increasingly incorporated into medical or education interventions, these domains are also starting to consider how to apply their familiar evaluation approaches to AI technologies [e.g., in healthcare, 134,170][e.g., in education, 36], and how to translate insights from RAI to their evaluation practices [e.g.…”
Section: Evaluation Goals and Approaches Outside Of Hcimentioning
confidence: 99%
“…The present study aligns primarily with the third category, as M-Shule is an SMS-based platform to deliver educational content to learners, but also with the second category to an extent, as caregiver support is also required for young learners to access and make use of mobile devices. Kizilcec et al (2021) present a study based on an analysis of platform usage data from a different SMS-based system, Shupavu291. Developed by Eneza Education, Shupavu291 delivers curriculum-linked educational materials and quizzes to learners, and allows questions to be submitted to teachers, via SMS (Kizilcec & Goldfarb, 2019).…”
Section: Recent Sms Implementations In M-learningmentioning
confidence: 99%
“…The study sought insights into educational disruption and mobile learning through the analysis of usage data from a previous period of school closures in Kenya in 2017, relating to political unrest. It showed that use of the platform increased during periods of disruption, and there was slightly different user demand; for example, learners often make greater use of quizzes in the run-up to exams, but during disruption, there was more emphasis on accessing content (Kizilcec et al, 2021).…”
Section: Recent Sms Implementations In M-learningmentioning
confidence: 99%
“…A second article, by René Kizilcec, Maximillian Chen, Kaja Jasińka, Michael Madalo, and Amy Ogan (Kizikcec et al, 2021; “Mobile Learning During School Disruptions in Sub-Saharan Africa”), also uses technology to acquire new data and new treatments. This work investigates how mobile learning technologies helped offset social disruptions to schooling for over 1.3 million students in sub-Saharan Africa.…”
Section: Presentmentioning
confidence: 99%